Study on the relation between mineral compositions of rock and construction characteristics of tunnel in cold regions: a case - Shang, Yanliang; Du, Shouji; Gao, Honghong; Han, Tongyin (Penerbit Universiti Kebangsaan Malaysia, 2017)
Mineral composition of rock has a very important influence on the physical and mechanical properties of tunnel surrounding rock. Take Dangjianshan tunnel in cold regions for example, the rock specimens in different parts of tunnel were taken to carry out the detection test of mineral composition. By the detail qualitative and quantitative analysis, the relationship between mineral composition and surrounding rock engineering properties was explored. First of all, the composition and content of minerals contained in in the rock specimens were detected by X ray fluorescence spectrometer and X ray powder diffraction. The detection results show that rock of tunnel contains high hardness minerals such as quartz and feldspar which were proven by initial engineering geological investigation report, in addition, it also contains several kinds of low hardness minerals including inclined chlorite and illite which may exhibit large deformation characteristic of soft rock after the tunnel excavation in case of meeting water and weathering conditions. The total content of inclined chlorite and illite accounted for a considerable component in main tunnel, inclined shaft and parallel pilot respectively and the influence on surrounding rock engineering properties cannot be ignored. Therefore, mineral composition detection must be paid attention to after tunnel excavation. Secondly, the effects of mineral composition on surrounding rock were analyzed in aspects of rock strength, weathering resistance, water softening property and excavation deformation through comparing the rock samples in different parts of tunnel. The comparative results showed that when the mineral contents is high with high hardness and poor hydrophilicity, tunnel surrounding rock plays a better performance of physical and mechanical properties, vice versa. Finally, according to the specific geological and construction parameters of the tunnel, the correlation analysis was studied about the vault settlement after tunnel excavation and the hydrophilicity mineral content in main cave. The logarithmic relationship between them was found and the correlation coefficient was 0.98. It can provide a useful reference for the settlement prediction of Dangjinshan tunnel construction.